Location and associated clinical characteristics of colon cancer. Hospital Nacional Arzobispo Loayza: 2009 - 2013 - Machicado Zuñiga, Enrique (2015)
Objective: To determine the association between the clinical characteristics and the location of colon cancer in patients hospitalized at "Hospital Nacional Arzobispo Loayza", during May 2009 - September 2013. Material and Methods: transversal study of 144 patients with primary colon cancer, of which 42 patients met the inclusion criteria; hospitalized in the 6-II Wing of the Department of General Surgery at "Hospital Nacional Arzobispo Loayza", between May 2009 and September 2013. Results: the mean age was 60.5 years, and 66.7% of the cases were women. 100% of histologic types were adenocarcinoma. The right colon was affected in 61.9% of the cases; the left colon in 33.3%, and a mixed location in 4,8%. Regarding the topography, 33,3% of the cases were found in the ascending colon and 21,4% in the sigmoid colon. The most frequent symptoms were abdominal pain (76.2%), weight loss (69%) and anemia (64%). For right colon cancer, fatigue was 13 times more likely to appear, and anemia was 4.44 times more likely (p< 0.05). Conclusion: the most common location for cancer was in the right colon, and it was associated significantly with the presence of fatigue and anemia among the clinical characteristics. The most frequent symptoms were abdominal pain and weight loss, in any location. All cases were adenocarcinoma.